Grammatical Errors Committed by Students of Mts Nurul Huda Sawo in Writing Descriptive Texts - Ailinah, Banika Nur (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
This research was done to investigate the grammatical errors on descriptive texts written by the learners. Grammatical errors were analyzed based on Dulay, Burt, and Krashen’s surface strategy taxonomy. It consisted of four types of grammatical errors, namely omission, addition, misformation, and misordering. 30 students of the eighth grade students of MTs. Nurul Huda were the subjects of this research. The aims of this research were to know the kinds of grammatical errors and the grammatical error mostly committed by the students in writing descriptive texts. Qualitative was chosen as the research design. Analysis and writing test result were used as the instruments of the data collection. The result of this research indicated that there were 67 grammatical errors committed by the students. Misformation error was the highest percentage with 57.98%. Followed by Omission error was with 34.79%. Addition error was in the third place with 4.35%. While, the lowest mistake that the learners made was Misordering error (2.88%). Based on the findings, the teacher should pay attention to the students’ mistakes, especially on grammatical errors and push the learners to learn more about grammar.